Salinity in drinking water and blood pressure status of adolescent school children in coastal area of Bangladesh (Journal of Preventive and Social Medicine, 2021)
Background: High dietary salt intake from food is a major risk factor for raised blood pressure (BP) worldwide.  In the context of Bang ladesh , information regarding salinity in water and blood pressure especially in the  adolescent population is very scarce.  This study  was conducted  to  assess  the  blood  pressure  status  of  adolescent  school  children in coastal area of Bangladesh.Methods: A one-year school based cross-sectional study was carried out among 528 students of class 8-10 at schools of Bajua Union, Dacope Upazilla, saline prone zone of Khulna district. Relevant data were collected by using pre tested semi-structured questionnaire with face to face interview & checklist. Blood pressure was mea sured in a controlled environment and Collected water sources were analyzed by DPHE, Water Testing Laboratory. The study was conducted in the schools of Bajua Uni on, Dacope Upa zilla of the saline prone zone of Khulna district in between a one-year time frame.Results:  Among 528 participants most of them  were male (353, 66.9%) with an age of 14 years (185  ,  35.0%).  Most of them were read in class 8 (185 , 35.0%). Prevalence of paternal, maternal, paternal grandparents' and maternal grandparents' history of hypertension were found significant. About 72.3% regularly took extra salt during meal and 43.9% took salt preserved fish with  meal. Mean of systolic blood  pressure  of respondents were 114.2197 ± 7.61448  mm of Hg. Mean of diastolic blood pressure of respondents were 75.1 780 ± 5.45959 mm of Hg. Mean of pulse pressure of respondents were 39.0417 ± 6.56430. Mean of mean arterial pressure of respondents  were 88. I 9  I 9  ±  5.44267 mm of Hg. Sodium concentration of pond were approximately in between 500-600 mg/I, whereas in  tube  wells approximately in between 700-1 I 00 mg/I.Conclusion: Drinking water sodium is an important source of daily sodium intake , and therefore a risk factor for increased BP in salinity prone coastal areas. This adds to the cardiovascular health risks associated with food sodium intake in Southeast Asian populations. Low- saline alternative drinking water sources could effectively help to prevent high BP and hypertension-related morbidity and mortality in these coastal populations. New technologies for the supply of such alternative sources, including safeguarding the microbial quality , should be further studied.JOPSOM 2020; 39(1): 60-66